Eucommia ulmoides Oliv. Leaf Extract Improves Erectile Dysfunction in Streptozotocin-Induced Diabetic Rats by Protecting Endothelial Function and Ameliorating Hypothalamic-Pituitary-Gonadal Axis Function. (29th July 2019) - Fu, Hui; Bai, Xue; Le, Liang; Tian, Dong; Gao, Hai; Qi, Li-xin; Hu, Ke-ping
Abstract : Erectile dysfunction (ED) is a major complication of diabetes mellitus. Eucommia ulmoides Oliv. is used as a traditional medicine for male impotence, but no systematic study has examined its effect on diabetes-associated ED. In this study, we investigated the effects of Eucommia ulmoides Oliv. leaf extract (EULE) on restoring erectile function in streptozotocin (STZ)-induced diabetic rats model. After 16 weeks of treatment, EULE administration had significantly increased intracavernosal pressure, nitric oxide (NO) levels, and cyclic guanosine monophosphate (cGMP) concentrations. Serum superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) levels were markedly higher and serum malondialdehyde (MDA) levels were lower in the EULE-treated groups than in the diabetic model group. EULE restored NO biosynthesis by significantly increasing protein kinase B (Akt) and endothelial NO synthase (eNOS) activation. Furthermore, EULE is likely to benefit the hypothalamic-pituitary-gonadal (HPG) axis, as it increased gonadotropin-releasing hormone (GnRH), follicle-stimulating hormone (FSH), luteinizing hormone (LH), and testosterone (T) concentrations as well as hormone receptors Gnrhr, Fshr, and Lhr expression levels. Hence, EULE attenuates oxidative stress, increases NO production, and activates the Akt-eNOS pathway to restore endothelial function; moreover, EULE enhances the HPG axis to improve erectile function. These results suggest that EULE may represent a new therapeutic avenue for diabetes-associated ED.